Qualidade de vida e coping ocupacional de enfermeiros - Sampaio, Cynthia Lima (2015)
The work environment has a total influence on people's quality of life, whether in the physical aspect or in human relations. The general objective of this study is to compare the quality of life and the occupational coping of the nurses of a general hospital, with bond and without employment bond. The study was carried out in a reference hospital in the public network of the State of Ceará, made up of 640 nurses, in which the sample was composed of 190 of them. An identification instrument, the WHOQOL-bref, and the Occupational Coping Scale were used. To perform the correlations analyzes, we used X2 test and to compare means: Student t, ANOVA and Tukey. The results were: the profile of nurses was of professionals with mean age of 36.04 years (± 10.35), acting in nursing for 9.05 years (± 9.54) and 8.41 years (± 9,62) in the hospital care; Family income of R $ 8410.11; The majority (60.5%) had specialization; 76.3% were cooperative and 23.7% were insolvent, 30% worked in the morning and in the afternoon and 27.9% worked at night, 51.6% worked in critical units and 48.4% worked in non-critical units. The weekly workload found was 47.16 hours (± 16.16). The means of the domains found were: social relations with 67.46, psychological with 66.69, physical with 65.88 and environment with 57.12. The coping mean values ​​found were 72.76 (± 12.5) for the control factor, 60.44 (± 13.25) for the avoidance factor and 38.73 (± 17.60) for the symptom management factor. The cooperative group was younger. For the bankrupt, the majority (27.3%) had income of R $ 45001,00 to R $ 6000,00. For the cooperative, the predominant income (39.3%) was R $ 3001.00 to R $ 4500.00. Regarding the weekly workload, there was a statistically significant difference between the groups (p <0.05). The majority of the participants (42.2%) worked 20-39 hours and the cooperative (46.9%), 40-59 hours. The quality of life of the participants (67.18 ± 11.00) presented a better average in relation to the cooperative (62.1767 ± 11.47), with emphasis on the physical domain and the environment. There is a statistically significant difference only for the avoidant factor, and this strategy is more adopted by the participants (65.92 ± 13.59). It is concluded that it is necessary to look at the health of the nurse working in the hospital health of Ceará, with actions that contribute to the emotional aspect of this professional and also in the improvements of working conditions and ties. The limitation of the study lies in having been performed in only one public hospital, suggesting further research.